Older community‐dwelling people's comparative optimism about falling: A population‐based telephone survey. (18th May 2012) - Dollard, Joanne; Barton, Christopher; Newbury, Jonathan; Turnbull, Deborah
Abstract : Aim:  To determine whether older community‐dwelling people underestimate their own perceived chance of falling compared with that of other older people (comparative optimism), and whether a history of falls is associated with comparative optimism. Method:  A sample of community‐dwelling South Australians aged ≥65 years ( n = 389) completed a computer‐assisted telephone interview about their 12‐month fall history, their perceived chance of falling and their rating of other older people's chance of falling. Results:  Respondents were comparatively optimistic about their chance of falling (Z =−8.1, P < 0.001). Those who had fallen in the last 12 months had a lower comparative optimism score (Z =−3.0, P < 0.003). Conclusion:  As older people were comparatively optimistic about their likelihood of falling, they might not find fall prevention messages relevant. When older people present with a fall, clinicians could provide fall prevention information consistent with how older people present themselves.